Educational priorities in Africa - Kajubi, W. Senteza (Prospects, 1973)
When over half the nation is illiterate and the people clamour for education; when public expenditure on education is mounting, but the number of children who are denied the right to education is increasing; when classroom techniques are autocratic and teachers are in short supply and inadequately trained; when government and private firms demand trained recruits, but unemployment is widespread and is increasing; when a country is poor, what policies should the national officials responsible for the planning of educational development pursue? Although these problems do not occur to the same extent in every country, it would be true to say that to a greater or lesser degree, all countries of the world are faced with the problem of the population explosion, and of the scientific and technical revolution, both of which have resulted in more people to be taught and more information to be learned, which have in turn caused an unprecedented and almost insatiable social demand for more and better education. However, despite public zeal and heavy investment in formal education, the gap between supply and demand for education in the various countries is wide and increasing, as is the gulf IV. Senteza Kajubi (Uganda). Director of the National Institute of Education, Makerere University, Kampala. Chairman of the Association for Teacher Education in Africa ( A TEA). 76 between the rich and the poorer countries of the world. About half of the world's population can neither write nor read, while only half of the children of primary school age receive more than a few years of schooling in most developing countries. Combined with this is the widening cleavage between country and town, and the inability of the economies of the developing countries to absorb readily the products of the schools. These, and similar problems, baffle policy makers and educational planners everywhere. How can the limited resources available for education be used to tackle these massive problems, and make a difference? The report of the International Commission on the Development of Education (I972) is a wide-angle lens covering a vast array of educational problems and zooming in on a number of the major issues related to educational development.